A comparative study between two techniques of subtotal laparoscopic cholecystectomy in goats: 1 M. A. Alkhilani; 2 M. J. Eesa; 2 S. I. Saleh; 3 A. A. Ajeel - Eesa, M. J. (The Iraqi Journal of Veterinary Medicine, 2014)
A comparison between two techniques of subtotal laparoscopic cholecystectomy was studied to find the best technique for treating severe cholecystitis and to study the fate of the remaining part of the gallbladder. All experimental animals had inducing cholecystitis by clipping the cystic duct for five days which was enough for inducing cholecystitis in goats. 24 adult female goats were used in this study, which were divided randomly into two equal groups; subtotal laparoscopic cholecystectomy with cystic duct and cystic artery clipping by titanium clips (group A) and laparoscopic subtotal cholecystectomy with cystic duct clipping only (group B). Operations were performed under general anesthesia by using thiopental sodium at a dose of 15 mg/Kg. B.W. intravenously to maintain the inhalation anesthesia by endotracheal tube with a mixture of halothane (1.5- 2.5 %) and oxygen (2-3 %). The intraabdominal pressure with CO2 was used at a low pressure 8-10 mmHg. The liver function tests including; alkaline phosphates (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), total serum bilirubin and C- reactive protein were measured in different intervals; before operation (zero day) and at 1hr, 1st, 3rd, 5th and 7th postoperative day. The liver function tests showed a significant elevation (P< 0.05) in alkaline phosphates (ALP) and in the total bilirubin values in group B (P> 0.05) comparison with group A and no significant difference in alanine aminotransferase (ALT), aspartate aminotransferase (AST) and C- reactive protein between all experimental groups as well as time intervals. The biopsies were taken at the 3rd, 7th and 15th postoperative day for histopathological of the remaining part of gallbladder which showed that subtotal cholecystectomies could be performed successfully with the two techniques, appeared degeneration in the remaining part of the gallbladder and offers best in the healing stages.